2015
DOI: 10.2134/cs2015-48-1-7
|View full text |Cite
|
Sign up to set email alerts
|

The water conundrum of planting cover crops in the Great Plains: When is an inch not an inch?

Abstract: Cover crop use is being widely promoted throughout the entire United States because of the potential benefits related to protecting and improving the soil. However, in semiarid environments such as the western and central Great Plains (where water is the single most limiting factor to crop production), cover crop water use may result in significant yield loss in following crops such as winter wheat. This article explores why many of the benefits associated with cover crop use may not be seen in this water‐limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 2 publications
1
27
0
Order By: Relevance
“…For all three crops, water use efficiencies were greater in the Northern Great Plains (lesser pan evaporation) than in the Central Great Plains (greater pan evaporation). Likewise Robinson and Nielsen (2015) showed increasing intercepts and decreasing slopes of water use/yield production functions (indicating decreasing water use efficiency) of wheat ( Triticum aestivum L.) and corn ( Zea mays L.) as location changed from Northern to Southern Great Plains with concomitant increasing pan evaporation (relationships from Brown, 1971; Nielsen et al, 2011; C. Robinson, personal communication, 15 Dec. 2014). Therefore, transferring cover crop production results from the nNorthern Great Plains to the higher evaporative demand environment of the Central and Southern Great Plains should be done with some caution.…”
Section: Water Use Efficiency (Kg Ha−1 Mm−1) Of Seed Production For Pmentioning
confidence: 99%
See 1 more Smart Citation
“…For all three crops, water use efficiencies were greater in the Northern Great Plains (lesser pan evaporation) than in the Central Great Plains (greater pan evaporation). Likewise Robinson and Nielsen (2015) showed increasing intercepts and decreasing slopes of water use/yield production functions (indicating decreasing water use efficiency) of wheat ( Triticum aestivum L.) and corn ( Zea mays L.) as location changed from Northern to Southern Great Plains with concomitant increasing pan evaporation (relationships from Brown, 1971; Nielsen et al, 2011; C. Robinson, personal communication, 15 Dec. 2014). Therefore, transferring cover crop production results from the nNorthern Great Plains to the higher evaporative demand environment of the Central and Southern Great Plains should be done with some caution.…”
Section: Water Use Efficiency (Kg Ha−1 Mm−1) Of Seed Production For Pmentioning
confidence: 99%
“…For example, they reported 518 g of water to produce a gram of alfalfa ( Medicago sativa L.) in Williston, ND, and 1005 g of water to produce a gram of alfalfa in Dalhart, TX. This difference is due to the evaporative demand differences that exist across the region as quantified by the strong north to south gradient of pan evaporation across the Great Plains (Tanner and Sinclair, 1983; Robinson and Nielsen, 2015; Farnsworth et al, 1982; Stewart and Peterson, 2014; Sinclair and Weiss, 2010). Tanner and Sinclair (1983) indicated that dry matter production was inversely related to pan evaporation.…”
Section: Water Use Efficiency (Kg Ha−1 Mm−1) Of Seed Production For Pmentioning
confidence: 99%
“…These forages, planted between traditional cropping sequences, can remove excess soil moisture in more humid areas, whereas, in semiarid and arid regions, cover crop impacts can range from increased to decreased soil moisture (Nielsen et al, 2015; Reese et al, 2014; Robinson and Nielsen, 2015). Winter cover crops can increase snow catch (CW, 2012; Dobberstein, 2016).…”
Section: Impacts Of Integrated Crop–livestock Systems On Crop Productmentioning
confidence: 99%
“…In those cases yield depressions were sometimes associated with emergence and stand establishment problems or N unavailability. In the results from the U.S northern Great Plains states and Canadian Prairie provinces, yields were not as frequently reduced by a prior cover crop and this is likely a result of the lower demand for water seen at those locations (Robinson and Nielsen, 2015)…”
Section: Previous Research On Cover Crop/previous Crop Effects On Yiementioning
confidence: 99%